294. AN UNUSUAL CASE OF EPIPHRENIC DIVERTICULUM COEXISTING WITHIN ESOPHAGEAL LEIOMYOMA. (24th September 2022) - Farooqui, Marryam Riaz; Rauf, Fatima; Bhatti, Hamza Waqar; Javed, Umer; Arshad, Rabia; Hanif, Muhammad
Abstract: Oesophageal leiomyoma and epiphrenic diverticulum are two rare entities to be simultaneously occurring together. The preoperative diagnosis in such coexisting conditions is often difficult and leiomyoma is mostly an incidental finding. Till date there is no evidence of the pathogenesis that if the diverticulum causes leiomyoma or vice versa?: We report a case of 32-year-old male with no known co-morbids, previous history of accidental kerosine oil intake 7 months ago, with dysphagia and retrosternal burning pain since 4 weeks with no history of documented weight loss. General physical and systemic examinations were unremarkable. Contrast studies showed left sided epiphrenic diverticulum. CECT was suggestive of traction diverticulum. Endoscopy showed a large diverticulum on left side of esophagous 38 cm from incisors. On laparoscopy a mass extending to GEJ was appreciated and patient underwent laparoscopy assisted transhiatal esophagectomy and esophagogastric anastomosis with feeding jejunostomy. Peroperatively a mass of 15 x 8 cm was arising from distal oesophagus histopathology of which came out to be a leiomyoma. On POD '0' patient developed Rt sided pneumothorax for which chest intubation was done. Repeat contrast studies showed a patent anastomosisand patient was discharged home. A careful history, thorough investigations, and surgeon's awareness of possible synchronous disease processes helps in the management of such patients.